Exploring Consumer Satisfaction and Service Quality at Bhatbhateni Supermarket - Nepali, Bijeta; Bhat, Chudamani Singh; Mahato, Bikesh Kumar (NPRC Journal of Multidisciplinary Research, 2024)
Background: Customer satisfaction and service quality are pivotal to the success of businesses, particularly in the competitive retail landscape of Kathmandu. Bhatbhateni, as one of the leading retail chains in Nepal, plays a crucial role in offering a wide array of products and services. Understanding customer perceptions regarding service quality and satisfaction is essential for enhancing operational strategies and maintaining a competitive edge in this dynamic market. Objectives: This study aims to analyze the demographic profile of Bhatbhateni’s customers, evaluate their perceptions of service quality and satisfaction, identify key service needs and expectations, and assess the likelihood of repurchase and recommendations among customers. Methods: A quantitative research approach was employed, utilizing structured questionnaires distributed to a sample of 120 customers of Bhatbhateni, selected through convenience sampling to ensure a diverse representation of gender and age. The questionnaire encompassed demographic inquiries and Likert scale items measuring customer satisfaction, service quality, and overall service experience. Data analysis involved descriptive statistics to summarize findings and identify trends in customer perceptions. Findings: The results indicated that the sample comprised 53.3% male and 46.7% female customers, with 61.7% of respondents aged between 15-25 years. A substantial 70.0% of respondents felt that Bhatbhateni understood their service needs effectively. In terms of satisfaction levels, 43.3% of customers reported being somewhat satisfied, while 12.5% expressed being very satisfied with the products. Moreover, 45.8% of respondents rated Bhatbhateni’s quality management as good, and 41.7% positively rated staff responsiveness. Additionally, 48.3% indicated a high likelihood of repurchasing products, and 61.7% stated they would likely recommend Bhatbhateni to others. Conclusion: The study reveals a generally positive perception of service quality among Bhatbhateni’s customers, highlighting key areas of strength and potential for improvement. Customer satisfaction is significantly influenced by the understanding of service needs and the quality of management. These findings suggest that Bhatbhateni is well-positioned for sustained growth through enhanced customer engagement and service delivery. Novelty: This research contributes valuable insights into the relationship between service quality and customer satisfaction within the specific context of Bhatbhateni, a prominent retail chain in Nepal. By employing a structured questionnaire and statistical analysis, the study adds to the limited existing literature on customer service perceptions in Nepal’s retail sector. The findings can guide Bhatbhateni and similar businesses in developing targeted strategies to improve customer satisfaction and loyalty, ultimately enhancing business service management practices in the region.